Highly crystalline mesoporous SSZ-13 zeolite obtained via controlled post-synthetic treatment. Issue 1 (20th December 2018) - Wardani, Maryani K.; Kadja, Grandprix T. M.; Fajar, Adroit T. N.; Subagjo,; Makertihartha, I. G. B. N.; Gunawan, Melia L.; Suendo, Veinardi; Mukti, Rino R.
Abstract : The role of remaining organics to control the extent of desilication. Abstract : The generation of mesoporosity in SSZ-13 zeolite by means of desilication via post alkaline treatment normally results in severe damage to the microporous framework hence giving an undesirable decline in catalytic performance. Herein, we propose a post-synthetic desilication treatment that is controllable with an aim to preserve the high crystallinity of SSZ-13 zeolite during the formation of mesopores. The extent of desilication in alkaline media is controlled by deliberately leaving the organics within SSZ-13 frameworks as they can effectively hinder the attack of hydroxyl ions on siloxane bonds. The resulting SSZ-13 exhibits substantial development of mesoporosity with preserved high crystallinity and microporosity that can then be used to relieve the mass transport issues and lead to an increased activity of LDPE pyrolysis.